Difference equations and inverse problems - Moyo, Donald (My University, 2023)
No abstract provided.
A dissertation submitted in partial fulfilment of the requirements for the degree of Master of Science to the Faculty of Science, School of Mathematics, University of the Witwatersrand, Johannesburg, 2023